Functional transient receptor potential vanilloid 1 and transient receptor potential vanilloid 4 channels along different segments of the renal vasculature. (21st August 2014) - Chen, L.; Kaßmann, M.; Sendeski, M.; Tsvetkov, D.; Marko, L.; Michalick, L.; Riehle, M.; Liedtke, W. B.; Kuebler, W. M.; Harteneck, C.; Tepel, M.; Patzak, A.; et al.
Abstract Aim Transient receptor potential vanilloid 1 (TRPV1) and vanilloid 4 (TRPV4) cation channels have been recently identified to promote endothelium‐dependent relaxation of mouse mesenteric arteries. However, the role of TRPV1 and TRPV4 in the renal vasculature is largely unknown. We hypothesized that TRPV1/4 plays a role in endothelium‐dependent vasodilation of renal blood vessels. Methods We studied the distribution of functional TRPV1/4 along different segments of the renal vasculature. Mesenteric arteries were studied as control vessels. Results The TRPV1 agonist capsaicin relaxed mouse mesenteric arteries with an EC50 of 25 nm, but large mouse renal arteries or rat descending vasa recta only at >100‐fold higher concentrations. The vasodilatory effect of capsaicin in the low‐nanomolar concentration range was endothelium‐dependent and absent in vessels of Trpv1 ‐/‐ mice. The TRPV4 agonist GSK1016790A relaxed large conducting renal arteries, mesenteric arteries and vasa recta with EC50 of 18, 63 nm and ~10 nm respectively. These effects were endothelium‐dependent and inhibited by a TRPV4 antagonist, AB159908 (10 μm). Capsaicin and GSK1016790A produced vascular dilation in isolated mouse perfused kidneys with EC50 of 23 and 3 nm respectively. The capsaicin effects were largely reduced in Trpv1 ‐/‐ kidneys, and the effects of GSK1016790A were inhibited in Trpv4 ‐/‐ kidneys. Conclusion Our results demonstrate that two TRPV channels have unique sites of vasoregulatory function in the kidney with functional TRPV1 having a narrow, discrete distribution in the resistance vasculature and TRPV4 having more universal, widespread distribution along different vascular segments. We suggest that TRPV1/4 channels are potent therapeutic targets for site‐specific vasodilation in the kidney.